ANALISIS SENTIMEN EKSPEDISI SICEPAT DARI ULASAN GOOGLE PLAY MENNGGUNAKAN ALGORITMA NAÏVE BAYES - Ayu Kusuma Dewi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Google Play is a very popular Android application administration, so that people in general can comment on anything. SiCepat is one of the cargo delivery administrations in Indonesia domiciled in Jakarta. As an online media client, SiCepat application clients are allowed to offer perspectives and write anything. The motivation behind this review is to test opinions about SiCepat's efforts in the Google Play app using Naive Bayes calculations. To play the characterizations, two classes of feelings are needed, namely the good class and the negative class. Information recovery was completed by the rejection method, the consequence of the information obtained was 457 positive and negative surveys. Then, at that time, the information was isolated into two, namely preparation information and test information. To guarantee essential testing with Nave Bayes settings to find possible results. Credulous Bayes is an information mining method of ordering information. The results showed that the accuracy was 80%, negative feelings 87% and good opinion 57%.